Music therapy during childbirth: Aiding pain relief, a systematic review (Research, Society and Development, 2024)
Objective: To present the foundations and evidence that support the application of music therapy as an effective therapeutic tool to help with labor pain. Methodology: The article is a bibliographical review, of the systematic review type, based on scientific publications indexed in the Medline, PUBMED, Scopus, Lilacs, BDENF and Web of Science databases. Following the inclusion and exclusion criteria, 12 articles were selected. Results: Through the analysis of the data found, it was possible to see that musical therapy has a positive influence and can reduce pain during childbirth. Furthermore, it reduces the level of anxiety and labor time, as it promotes emotional well-being, comfort and relaxation in the parturient woman. Conclusions: Based on available evidence, music therapy represents a valuable and accessible option for women seeking a more peaceful and less painful birth, highlighting its potential to complement and even replace traditional methods of pain relief during labor.